The concept of a quantitative sign formation for the internal restructuring of information resource data - Barannik, Vlad.; Parkhomenko, M.; Gurzhii, P.; Azatov, A.; Shaikhanova, A.; Tupytsya, I.; Karpiinski, M.; Pershin, A. (Springer, 2020)
Outlines steps to develop a method of forming a compact representation of the segmented images based on the detection of the two-component vector of tuples for linearized transformant. Dependencies for bit rates are compared in the case of processing the key frames of a saturated image stream using various compression methods. Identified modes that achieved delivery of the video stream in real time.
Keywords: video information; coding vectors tuples